Absence of Perilesional Neuroplastic Recruitment in Chronic Poststroke Aphasia. (12th July 2022) - DeMarco, Andrew Tesla; van der Stelt, Candace; Paul, Sachi; Dvorak, Elizabeth; Lacey, Elizabeth; Snider, Sarah; Turkeltaub, Peter E.
Abstract : Background and Objectives: A prominent theory proposes that neuroplastic recruitment of perilesional tissue supports aphasia recovery, especially when language-capable cortex is spared by smaller lesions. This theory has rarely been tested directly and findings have been inconclusive. We tested the perilesional plasticity hypothesis using 2 fMRI tasks in 2 groups of patients with previous aphasia diagnosis. Methods: Two cohorts totaling 82 patients with chronic left-hemisphere stroke with previous aphasia diagnosis and 82 control participants underwent fMRI using either a naming task or a reliable semantic decision task. Individualized perilesional tissue was defined by dilating anatomical lesions and language regions were defined using meta-analyses. Mixed modeling examined differences in activity between groups. Relationships with lesion size and aphasia severity were examined. Results: Patients exhibited reduced activity in perilesional language tissue relative to controls in both tasks. Although a few cortical regions exhibited greater activity irrespective of distance from the lesion, or only when distant from the lesion, no regions exhibited increased activity only when near the lesion. Larger lesions were associated with reduced language activity irrespective of distance from the lesion. Using the reliable fMRI task, reduced language activity was related to aphasia severity independent of lesion size. Discussion: We found no evidence for neuroplastic recruitment of perilesional tissue in aphasia beyond its typical role in language. Rather, our findings are consistent with alternative hypotheses that changes in left-hemisphere activation during recovery relate to normalization of language network dysfunction and possibly recruitment of alternate cortical processors. These findings clarify left-hemisphere neuroplastic mechanisms supporting language recovery after stroke.